2022
DOI: 10.1002/ps.7206
|View full text |Cite
|
Sign up to set email alerts
|

Systemic whitefly‐induced metabolic responses in newly developed distal leaves of husk tomato plants (Physalis philadelphica) impairs whiteflies development

Abstract: BACKGROUND: Metabolic reconfiguration in plants is a hallmark response to insect herbivory that occurs in the attack site and systemically in undamaged tissues. Metabolomic systemic responses can occur rapidly while the herbivore is still present and may persist in newly developed tissue to counterattack future herbivore attacks. This study analyzed the metabolic profile of local and newly developed distal (systemic) leaves of husk tomato (Physalis philadelphica) plants after whitefly Trialeurodes vaporariorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Husk tomato ( P. philadelphica ) seedlings are susceptible to infestation by the whitefly Trialeurodes vaporariorum . A newly published metabolome study showed that P. philadelphica impairs whitefly development by inducing significant changes in metabolic profiles ( Meza-Canales et al., 2022 ). Metabolomics researches provide us an opportunity to understand the differences in types and contents of active ingredients in Physalis plants.…”
Section: Application Of Omics In Physalis Studymentioning
confidence: 99%
“…Husk tomato ( P. philadelphica ) seedlings are susceptible to infestation by the whitefly Trialeurodes vaporariorum . A newly published metabolome study showed that P. philadelphica impairs whitefly development by inducing significant changes in metabolic profiles ( Meza-Canales et al., 2022 ). Metabolomics researches provide us an opportunity to understand the differences in types and contents of active ingredients in Physalis plants.…”
Section: Application Of Omics In Physalis Studymentioning
confidence: 99%